Pengaruh Flash Sale, Fear of Missing Out, dan Live Streaming terhadap Keputusan Pembelian pada Produk Skincare di TikTok Shop - Fitriana Salsabila Putri; Lilik Indayani; Misti Hariasih (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2025)
This study aims to analyze the level of effectiveness of using Flash Sale, Fear of Missing Out, and Live Streaming on purchasing decisions for skincare products at TikTok Shop. The method used in this research is quantitative, with data collected from 96 respondents through distributing questionnaires in the form of a list of questions. The data obtained is then processed using SmartPLS software. Respondents in this study are consumers who buy skincare products through TikTok Shop. The results showed that the use of Flash Sale, Fear of Missing Out, and Live Streaming had a strong and significant influence on purchasing decisions for skincare products at TikTok Shop